Genetic Liability to Sedentary Behavior in Relation to Stroke, Its Subtypes and Neurodegenerative Diseases: A Mendelian Randomization Study - Yang, Fangkun; Chen, Songzan; Qu, Zihao; Wang, Kai; Xie, Xiaojie; Cui, Hanbin (Frontiers in Aging Neuroscience, 2021)
Objective: To investigate the causal association of domain-specific sedentary behaviors with cerebrovascular diseases and neurodegenerative diseases, and the potential mediators among these associations. Methods: Genetic instruments were identified for television watching, computer use and driving behavior from a genome-wide association study including 408,815 subjects. Mendelian randomization (MR) analysis was used to estimate the causal effect of sedentary behaviors on the cerebrovascular diseases and neurodegenerative diseases. Multivariable MR analysis was applied to adjust potential confounding factors, and mediation analysis was conducted to explore potential mediators. Results: Genetically predisposition to 1.5 hour/day increase in leisure time watching television was associated with increased risk of all-cause stroke (odds ratio (OR) = 1.32, 95% confidence interval (CI) = 1.15 - 1.52, p-value for MR-Egger method (PEgger) = 0.11, I2 = 37%, Cochrane’s Q = 212, p-value for Cochran Q test (PQ) < 0.001), and ischemic stroke (OR = 1.28, 95%CI = 1.10 - 1.49, PEgger = 0.04, I2 = 35%, Cochrane’s Q = 206, PQ = 0.002). Interestingly, television watching may decrease the risk of Parkinson’s disease (OR = 0.65, 95%CI = 0.50 – 0.84, PEgger = 0.47, I2 = 19%, Cochrane’s Q = 157, PQ = 0.04). Television watching was a detrimental factor of cognitive performance (estimate = -0.46, 95%CI = -0.55 – -0.37, PEgger = 0.001, I2 = 85%, Cochrane’s Q = 862, PQ < 0.001). Sensitivity analyses using leave out method and MR-PRESSO method suggested weak evidence of pleiotropy. Conclusion: We provided genetic evidence for the causal association of television watching with increased risk of all-cause stroke and ischemic stroke, decreased risk of Parkinson’s disease, and worse cognitive performance. The results should be interpreted with caution considering the pleiotropy.